2018
DOI: 10.1590/1413-785220182602185594
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Patellar Tendon Autograft in Anterior Cruciate Ligament Reconstruction

Abstract: Objective:To conduct a systematic review of literature about the use of contralateral patellar tendon autograft in anterior cruciate ligament reconstructions and present the results. Methods:The LILACS, MEDLINE, Cochrane, PubMed, Scielo and Google Scholar databases were searched without date restrictions for the keywords “anterior cruciate ligament reconstruction” combined with “contralateral” in the article title. After the studies were identified, two independent evaluators collected the qualitative characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The procedures were based on previous studies. 30 , 44 , 45 All approaches were performed using the anatomic technique, via the medial portal, simultaneously in both knees (receptor and donor). A tourniquet was also used on both knees.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures were based on previous studies. 30 , 44 , 45 All approaches were performed using the anatomic technique, via the medial portal, simultaneously in both knees (receptor and donor). A tourniquet was also used on both knees.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies 6 , 30 , 36 demonstrated the clinical results of short- and medium-term recovery of patients who underwent ACL reconstruction with a contralateral bone–patellar tendon–bone (BPTB) graft and were rehabilitated under the same conditions as described by Shelbourne and Klotz. 45 The patients were satisfied with their function, but the isokinetic evaluation at multiple time points showed the presence of significant differences in muscle performance between each lower limb, of which the donor limb, (ie, the healthy limb), was shown to be more deficient.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Disadvantages of allograft include a slower incorporation rate, the potential for transmission of viral disease, and observations by some authors that there may be more residual laxity and less strength than with autologous reconstructions. Some investigators have concluded that autologous patellar tendon grafts should be the first choice, and that allografts should be suggested for revision surgery (new ACL tear already repaired) or when multiple grafts are needed due to complex instabilities; they are most effective when used in patients who perform low-intensity physical activity (8,(38)(39)(40).…”
Section: Graft Selectionmentioning
confidence: 99%
“…While the use of contralateral graft harvest in ACL revision surgery is not uncommon [1], few surgeons have adopted this approach in primary ACL‐R [2]. When comparing contralateral and ipsilateral graft harvest, it has previously been reported that no differences at short‐term follow‐up were found in morbidity with both patellar bone tendon bone and semitendinosus and gracilis (STG) grafts [3, 4].…”
Section: Introductionmentioning
confidence: 99%